The Impact of Financial Crises on Labor Markets, Household Incomes, and Poverty : A Review of Evidence - Fallon, Peter R.; Lucas, Robert E. B. (World Bank, Washington, DC, 2014)
The 1990s have witnessed several financial crises, of which the East Asia and Mexico tequila crises are perhaps the most well-known. What impact have these crises had on labor markets, household incomes, and poverty? Total employment fell by much less than production declines and even increased in some cases. However, these aggregates mask considerable churning in employment across sectors, employment status, and location. Economies that experienced the sharpest currency depreciations suffered the deepest cuts in real wages, though deeper cuts in real wages relative to Gross Domestic Product (GDP) were associated with smaller rises in unemployment. To some extent, families smoothed their incomes through increased labor force participation and private transfers, though the limited evidence available suggests that wealthier families were better able to smooth consumption. The initial impact of the crises was on the urban corporate sector, but rural households were affected as well and in some instances suffered deeper losses than did urban families. School enrollment declined, especially among poorer families, as did use of health facilities, but the impact on children's nutrition levels appears to vary. Crises have typically proved short-lived, but whether households plunged into poverty during a crisis is able to recover as the economy does remain an open question.